Penguatan Tata Kelola dan Pemasaran Olahan Salak untuk Wisatawan Mancanegara - Ichsan, Muchammad; Widyastuti, Titiek (Universitas Muhammadiyah Yogyakarta, 2017)
Marketing of souvenir products in the form of snacks for tourism services is an important thing especially for foreign tourists. Without good marketing tourists will not know that souvenirs become an alternative for tourists visiting Sleman. Souvenirs in the form of processed salak food into alternative tourists who visit Yogyakarta other than gudeg, bakpia, geplak and so on. During this cultivation of marketing processed salak products produced by small usha group has not been done optimally, just merely dititipkan on certain stalls. The problem has been resolved by the existence of community service program with PKM scheme. Through the training of governance and marketing, the preparation of business plans and also various innovations memdia promotion can develop business pondak salak processing to foreign tourists. Besides, by giving English-language promotional media getting closer to foreign tourists. For prospective buyers who from abroad also prepared an English brochure containing prouduk specifica-tion and price. Management assistance activities have also been conducted regularly every week. The results of this program include making leaflets, English packaging and English web. The benefits gained from both â€œCrystalâ€ and â€œJewelâ€ partners are that they have been able to penetrate the foreign tourist market. This means increasingly open new market opportunities and can be the pride of the Sleman community.Keywords: governance, marketing, processed of â€œsalakâ€ fruit.